Function of Topeng Tunggal Dance in Betawi Society - Sabillah, Kholifah; Dewi, Maharani Luthvinda; Putro, Renaldi Lestianto Utomo (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2025)
The Topeng Tunggal Dance is a traditional Betawi art form created by Mak Kinang and Kong Djiun in 1930. The inception of the Topeng Tunggal Dance was inspired by a vision experienced by Mak Kinang, which was subsequently brought to life through dance and musical accompaniment by Kong Djiun. This research aims to explore and understand the values and functions inherent in the Topeng Tunggal Dance. The methodology employed in this study is qualitative, utilizing an analytical descriptive approach and the functional theory of RM. Soedarsono. Data collection techniques include observations, interviews with artists, and documentation. The findings indicate that the Topeng Tunggal Dance embodies two primary values: moral and aesthetic. Additionally, this dance serves three functions: as entertainment, as a performing art, and as a medium for education. These values and functions position the Topeng Tunggal Dance not only as a cultural heritage but also as a means for character development and the preservation of the cultural identity of the Betawi people.